SENI HADROH SEBAGAI MEDIA DAKWAH REMAJA (STUDI AKTIVITAS KEAGAMAAN IRMAS DESA MANTIASA KECAMATAN TEBING TINGGI BARAT) - Nur Rohman; Nunu Burhanuddin (Jurnal Komunikasi, 2023)
Islam is a religion of da'wah, where the Islamic religion itself encourages its adherents to always be active in spreading the religion of Islam. The progress or decline of Muslims really depends on how they preach. Da'wah itself can be done verbally, bil- qalam, bil hal and also in forums as long as the aim is to invite goodness and commands of Allah SWT and to imitate the Prophet Muhammad. Through modern art filled with prayers praising Rasullulah accompanied by hadroh music, it will attract teenagers in general in increasing the religious activities carried out by the El- Fata Hadroh Group. This research starts from a background where before the hadroh appeared or was formed, teenagers were still lacking in enlivening the mosque, but after the hadroh appeared, the teenagers began to be interested in joining the hadroh community. After these teenagers join, they are easier to direct, and know the extent to which hadroh has been used as a medium for youth da'wah in fostering a spirit of religious activity in Mantiasa Village, Batang Suntai Hamlet, West Tebing Tinggi District. This research uses qualitative research. Data collection uses observation, interviews and documentation methods. Through interview and observation methods, it is known that the main subjects to be researched are teenagers who are members of the Hadroh El-Fata group. From the results of research conducted by researchers, it shows that the teenagers of Mantiasa Village, Batang Suntai Hamlet are enthusiastic about carrying out religious activities. The religious activities carried out by the teenagers of Mantiasa Village are sholawat, Muizotul Hasanah, learning to read the Al-Qur'an, learning speeches and praying, with Mauizotul Hasanah and good spiritual guidance can influence the morals of teenagers who have followed this hadroh. With this gift, teenagers' time is not wasted, teenagers' free time is used with positive activities that are useful for changing their personality for the better